Spinal Stroke following Kidney Transplant - Jayanthan B. Subramanian; Farjad Siddiqui; Pranit N. Chotai; Yazan Al-Adwan; Amer Rajab; Kenneth Washburn; Austin D. Schenk; Ashley J. Limkemann; Michael Luttrull; Musab Al-Ebrahim; Ginny Bumgardner; Navdeep Singh (Case Reports in Transplantation)
Complications are a part of surgery. Spinal infarctions are a dreaded complication of aortic surgery. We present a patient who developed a spinal infarct after a kidney transplant. We were unable to find a causative factor in our search for etiology. In our review of the literature, we were unable to find a similar report. We present this case report to highlight a rare complication of kidney transplantation and to reinforce that patients requiring kidney transplant are complex patients with multiple comorbidities that can cause a multitude of complications in the periop period.